β-nadh diminui a sensibilidade da sucinato desidrogenase a inibição por ácido metilmalônico - Torres, Aledson Rosa (2007)
Methylmalonic acidemia, one of the most frequent organic acidemias, is caused by deficiency of the methylmalonyl CoA mutase, leading to tissue accumulation of Lmethylmalolonic acid (MMA). Affects individuals present lethargy, coma, vomiting, muscular hypotonia, recurrent episodes of metabolic acidosis and progressive encephalopathy. In this context, it has been proposed that MMA inhibits succinate dehydrogenase (SDH) and leads to ATP depletion, lactate accumulation and excitotoxic damage. In the present study we confirmed that MMA competitively inhibits of SDH, and later were investigated the enzymatic medium reduction alters the activity of SDH or its inhibition by MMA. SDH activity was determined in cerebral cortex homogenates, using 2-(p-iodophenyl)-3-(p-nitrophenyl)-5-phenyltetrazolium chloride (INT), as the electorn acceptor. The reduction enzymatic medium was promoted by preincubation with β-NADH (160 μM). The preincubation of β-NADH prevented the inhibition of the activity of SDH induzed by 5mM of the MMA [F(1,5)=9.31; p=0.028]. In addition, was determined of the kinetic parameters (Km and Vmax) and inhition constant (Ki ) of SDH preincubated in the presence and absence of β-NADH. The Km of SDH preincubated with β-NADH (Km=0.216 nmol INT) was different of the Km of SDH preincubated in the absence of the β-NADH (Km=0.272nmol INT) [T(2)=10.375; p=0.009]. The presence of β-NADH in the incubation medium did not alter Vmax= 4.72 ± 0.28.10-8 mol INT/mg protein/min) [T(2)=-1.0; p=0.423]. The Ki of the MMA by SDH activity in presence of the β- NADH (Ki =20.05 mM) is increased that of Ki of the MMA by SDH activity in absence of the β-NADH (Ki =11.60 mM), [T(2)=18.806; p=0.003]. In conclusion, we showed that, in the presence of β-NADH, SDH is less sensitive to the inhibition by MMA.